A Study On The Impact Of The Working Capital Management On The Profitability Of The Leading Listed Automobile Companies In India (2006- 2012). (International Journal of Scientific Research and Management (IJSRM), 2017)
India’s strategic objective for the manufacturing sector in the next 15 years should be to bring about quantitative and qualitative change through a set of policies and plans. Therefore, the cost associated with the strategy of doing business is much higher in India. Hence to overcome the difficulty and meet the challenges of manufacturing sector in India, Industries are encouraged to attract more investments into the stream in order to minimize the risk of liquidity and to maximize profitability. The liquidity and profitability trade off can be tackled efficiently by improving and adopting effective working capital management strategies into the manufacturing sector. This study takes into consideration the top S&P CNX 500manufacturing firms within the geographical area of India. The automobile sector accounts for 7.1 per cent of the country’s gross domestic product (GDP). Working capital management is an important function of financial management which helps in maintaining an optimal balance between each of the working capital components. Industries can reduce their financing costs or increase the funds available for expansion of projects by minimizing the amount of investment tied up in current assets. In a broad-spectrum, current assets are considered as one of the important component of total assets of a firm. The purpose of the research is to analyze whether working capital management can affect the company profitability of Automobile sector in India. Some Previous research might have studied the relation between working capital management and profitability, but those research failed to address the Sectorwise issues of working capital management. This study aims at fulfilling such gaps by considering the industry specific nature of working capital. This thesis will introduce the reader about diverse techniques used to measure working capital management. Previous studies in this area have used various methods to measure the effectiveness of working capital. This study has been framed to show how efficient working capital management impacts the corporate profitability of 10 leading listed automobile sector in Chennai (India). The main source of secondary data was collected through Government reports, official records, journals, books, websites of Internet and financial statements, such as income statements, balance sheets of S&P CNX top500 companies at NSE were collected for the period of 2006 – 2012 from CMIE Prowess Database.